- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,841

$\dfrac{1}{\sin^2 \lambda}=\dfrac{1}{\sin^2 \alpha}+\dfrac{1}{\sin^2 \beta}+\dfrac{1}{\sin^2 \gamma}$

- Thread starter anemone
- Start date

- Thread starter
- Admin
- #1

- Feb 14, 2012

- 3,841

$\dfrac{1}{\sin^2 \lambda}=\dfrac{1}{\sin^2 \alpha}+\dfrac{1}{\sin^2 \beta}+\dfrac{1}{\sin^2 \gamma}$

- Jan 25, 2013

- 1,225

$\dfrac{1}{\sin^2 \lambda}=\dfrac{1}{\sin^2 \alpha}+\dfrac{1}{\sin^2 \beta}+\dfrac{1}{\sin^2 \gamma}$

Last edited:

- Thread starter
- Admin
- #3

- Feb 14, 2012

- 3,841

Solution provided by other:

First we let AP meet BC at X.

Since $\angle XBP=\angle BAX=\lambda$ and $\angle BXP=\angle AXB=\text{common angle}$, we can say that triangle XPB and XBA are similar. Then we have $\dfrac{XB}{XP}=\dfrac{XA}{XB}$

Applying the sine law to the triangle XBA and considering the fact that $\dfrac{XB}{XP}=\dfrac{XA}{XB}$ give us

$\dfrac{\sin \lambda}{\sin \beta}=\dfrac{XB}{XA}$

$\dfrac{\sin^2 \lambda}{\sin^2 \beta}=\dfrac{XB^2}{XA^2}=\dfrac{XAXP}{XA^2}= \dfrac{XP}{XA}$

Now, the ratio of the area of the triangles XPB to XBA and triangles XCP to XCA are

$\dfrac{\text{area of the triangle XPB}}{\text{area of the triangle XBA}}=\dfrac{XP}{XA}$ and

$\dfrac{\text{area of the triangle XCP}}{\text{area of the triangle XCA}}=\dfrac{XP}{XA}$

This tells us $\dfrac{\text{area of the triangle XPB}}{\text{area of the triangle XBA}}=\dfrac{\text{area of the triangle XCP}}{\text{area of the triangle XCA}}=\dfrac{\text{area of the triangle BPC}}{\text{area of the triangle ABC}}$

$\therefore \dfrac{\sin^2 \lambda}{\sin^2 \beta}=\dfrac{\text{area of the triangle BPC}}{\text{area of the triangle ABC}}$

By the similar arguments, we have

$\therefore \dfrac{\sin^2 \lambda}{\sin^2 \alpha}=\dfrac{\text{area of the triangle APB}}{\text{area of the triangle ABC}}$

$\therefore \dfrac{\sin^2 \lambda}{\sin^2 \gamma}=\dfrac{\text{area of the triangle CPA}}{\text{area of the triangle ABC}}$

Hence,

$\small\dfrac{\sin^2 \lambda}{\sin^2 \alpha}+\dfrac{\sin^2 \lambda}{\sin^2 \beta}+\dfrac{\sin^2 \lambda}{\sin^2 \gamma}=\dfrac{\text{area of the triangle APB}}{\text{area of the triangle ABC}}+\dfrac{\text{area of the triangle BPC}}{\text{area of the triangle ABC}}+\dfrac{\text{area of the triangle CPA}}{\text{area of the triangle ABC}}=1$

$\dfrac{1}{\sin^2 \lambda}=\dfrac{1}{\sin^2 \alpha}+\dfrac{1}{\sin^2 \beta}+\dfrac{1}{\sin^2 \gamma}$ (Q.E.D.)